Long non-coding RNAs: Potential therapeutic targets for epilepsy - Liu, Sen; Fan, Min; Ma, Meng-Die; Ge, Jin-Fang; Chen, Fei-Hu (Frontiers in Neuroscience, 2022)
Epilepsy is a common and disastrous neurological disorder characterized by abnormal firing of neurons in the brain, affecting about 70 million people worldwide. Long noncoding RNAs (LncRNAs) are a class of RNAs longer than 200 nucleotides without the capacity of protein coding, but they participate in a wide variety of pathophysiological processes. Regarding their role in epileptogenesis, alternated abundance and diversity of LncRNAs have been found in epilepsy patients and animal or cell models. This review will introduce the structure and function of LncRNAs, summarize the role of LncRNAs in the pathogenesis of epilepsy, especially its linkage with neuroinflammation, apoptosis, and transmitter balance, which will throw light on the molecular mechanism of epileptogenesis, and accelerate the clinical implementation of lncRNAs as a potential therapeutic target for the treatment of epilepsy.